The UPR sensor IRE1α promotes dendritic cell responses to control Toxoplasma gondii infection. (15th February 2021) - Poncet, Anaïs F; Bosteels, Victor; Hoffmann, Eik; Chehade, Sylia; Rennen, Sofie; Huot, Ludovic; Peucelle, Véronique; Maréchal, Sandra; Khalife, Jamal; Blanchard, Nicolas; Janssens, Sophie; Marion, Sabrina
Abstract: The unfolded protein response (UPR) has emerged as a central regulator of immune cell responses in several pathologic contexts including infections. However, how intracellular residing pathogens modulate the UPR in dendritic cells (DCs) and thereby affect T cell‐mediated immunity remains uncharacterized. Here, we demonstrate that infection of DCs with Toxoplasma gondii ( T. gondii ) triggers a unique UPR signature hallmarked by the MyD88‐dependent activation of the IRE1α pathway and the inhibition of the ATF6 pathway. Induction of XBP1s controls pro‐inflammatory cytokine secretion in infected DCs, while IRE1α promotes MHCI antigen presentation of secreted parasite antigens. In mice, infection leads to a specific activation of the IRE1α pathway, which is restricted to the cDC1 subset. Mice deficient for IRE1α and XBP1 in DCs display a severe susceptibility to T. gondii and succumb during the acute phase of the infection. This early mortality is correlated with increased parasite burden and a defect in splenic T‐cell responses. Thus, we identify the IRE1α/XBP1s branch of the UPR as a key regulator of host defense upon T. gondii infection. SYNOPSIS: Infection of dendritic cells with Toxoplasma gondii triggers the IRE1α pathway in a MyD88‐dependent manner, a process required to promote T cell responses and to control parasite dissemination in infected mice. Infection of dendritic cells with T. gondii triggers the induction of the IRE1α pathway in a MyD88‐dependent manner. T. gondii infection of dendritic cells leads to the downregulation of the ATF6 and CHOP pathways. IRE1α pathway activation in splenic cDC1 subsets regulates T cell activation and controls parasite dissemination. Abstract : Infection of dendritic cells with Toxoplasma gondii triggers the IRE1α pathway in a MyD88‐dependent manner, a process required to promote T cell responses and to control parasite dissemination in infected mice.